Relationship of Organizational Culture and Leadership Style on Performance of Z Generation in Startup Company on SBM ITB (Journal of Innovation, Business and Entrepreneurship, 2020)
Culture is regularly reenacted and generated by our experiences with others. Formed value of others, we think of that as "leadership" and are creating the conditions for new culture creation. Culture and leadership are two sides of the same coin in that leaders first initiate the sequence of culture formation when they create entities and organizations. Leadership may also be regarded as a critical factor in bringing about a profitable business for the company. However, a leadership style is usually used by a manager to fulfil their responsibilities and duties within the business and organization. The main purpose of this research is to determine how organizational culture can influence the leadership style, the relation of leadership style, the relationship between organizational culture and Z generation performance, and what type of leadership style may contribute to the performance of Z generation. After all, this has been established, and the aim is to find the best combination since these features in order to improve employee performance in general and especially in Z generation. As a possible consequence, overall performance can be continued to improve in the organization.Keywords: Leadership, Leadership Style, Organization, Employee Performance, Z generation